Assessment of a sitting position by means of a kyphotisation indicator in the professionally active people - Gruca, Maria; Saulicz, Edward (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The development of modern technology has changed human lifestyle from active to passive (sitting). According to many authors, prolonged sitting is a risk factor for overextension and painful conditions of the spine. However, it seems that this relationship can only occur in conjunction with other factors. The aim of this study is to assess a sitting position using a kyphotisation indicator constructed by the author. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study included 372 people living and working professionally in the Silesian Voivodeship. The research program consisted of an interview survey and measurements the length of the spine projections, which provided the calculation of a kyphotisation indicator. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The conducted assessment showed that the examined people receive automatically a kyphotic sitting position and this postural habit is moved to a standing position. In addition, the study highlighted the 2 types of habitual sitting positions, one with a higher kyphotisation indicator and the other with a lower kyphotisation indicator, reflecting the “dynamic” sitting and searching a comfortable (antalgic) sitting position by the researched people. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. A kyphotic sitting position is a risk factor for overextension and painful conditions of the spine, and the kyphotisation indicator can be a useful tool for further clinimetric research regarding a sitting position.